Transcriptome analysis reveals the potential contribution of long noncoding RNAs to brown adipocyte differentiation - Liang hui You; Li jun Zhu; Lei Yang; Chun mei Shi; Ling xia Pang; Jun Zhang; Xian wei Cui; Chen bo Ji; Xi rong Guo (Molecular Genetics and Genomics, 2015)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Effects of glucose, insulin and triiodothyroxine on leptin and leptin receptor expression and the effects of leptin on activities of enzymes related to glucose metabolism in grass carp (Ctenopharyngodon idella) hepatocytes - Rong-Hua Lu; Yi Zhou; Xiao-Chen Yuan; Xu-Fang Liang; Liu Fang; Xiao-Li Bai; Min Wang; Yu-Hua Zhao (Fish Physiology and Biochemistry, 2015)

Application of Lactic Acid Bacteria (LAB) in freshness keeping of tilapia fillets as sashimi - Rong Cao; Qi Liu; Shengjun Chen; Xianqing Yang; Laihao Li (Journal of Ocean University of China, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

Altered Functional Connectivity Patterns of the Insular Subregions in Psychogenic Nonepileptic Seizures - Rong Li; Kai Liu; Xujing Ma; Zhiqiang Li; Xujun Duan; Dongmei An; Qiyong Gong; Dong Zhou; Huafu Chen (Brain Topography, 2015)

Spiculisporic acid analogues of the marine-derived fungus, Aspergillus candidus strain HDf2, and their antibacterial activity - Rong Wang; Zhi Kai Guo; Xiang Min Li; Fu Xiao Chen; Xia Fei Zhan; Ming Hui Shen (Antonie van Leeuwenhoek, 2015)

Quantifying synoptic eddy feedback onto the low‐frequency flow associated with anomalous temperature events in January over China - Gui‐Rong Tan; Hong‐Li Ren; Haishan Chen (International Journal of Climatology, 2015)
Using a linear dynamic operator and the daily National Centers for Environmental Prediction/National Center for Atmospheric Research ( NCEP / NCAR ) reanalysis data, the linearized part of the synoptic eddy feedback onto the low‐frequency flow ( SELF ) associated with cold/warm events in January over China is investigated. Composite stream function differences between the cold and warming events show that the anomalous temperature events are linked closely to the teleconnection pattern which is related to North Atlantic Oscillation ( NAO ) and accompanied with remarkable anomalies over Ural Mountain and the areas south to Lake Baikal. The significant eddy feedback exists as the episodes occur, which tends to induce a similar circulation pattern to the anomalous low‐frequency flow associated with the temperature episodes. Further, a linear SELF operator is used to estimate quantitatively the linearized part of the eddy feedback on the low‐frequency flow for the temperature events. Results show that the magnitude of the stream function anomalies ( SFAs ) induced by eddy forcing is bigger at higher latitudes than lower latitudes. The positive (negative) SFA can be induced where eddy‐vorticity fluxes converge (diverge) into the anomalous cyclonic (anticyclonic) circulation. Further analysis of differences in eddy feedback strength suggests that synoptic eddy feedback is more effective for the cold events than that for the warm events over North Atlantic, Ural Mountain, and the areas south to Lake Baikal. The SFA anomaly pattern over Ural Mountain and Lake Baikal associated with the anomalous temperature events in China will disappear without considering the eddy feedback. It suggests that the eddy feedback plays a very important role in maintaining the low‐frequency flow during the January anomalous temperature events.

SKF-96365 strongly inhibits voltage-gated sodium current in rat ventricular myocytes - Kui-Hao Chen; Hui Liu; Lei Yang; Man-Wen Jin; Gui-Rong Li (Pflügers Archiv - European Journal of Physiology, 2015)

Molecular cloning, characterization and expression of the energy homeostasis-associated gene in piglet - Sheng-ping Wang; Yun-ling Gao; Gang Liu; Dun Deng; Rong-jun Chen; Yu-zhe Zhang; Li-li Li; Qing-qi Wen; Yong-qing Hou; Ze-meng Feng; Zhao-hui Guo (Journal of Zhejiang University-SCIENCE B, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

Flavobacterium shanxiense sp. nov., Isolated from Soil - Fan Yang; Hong-ming Liu; Rong Zhang; Ding-bin Chen; Xiang Wang; Xin Yan; Qing Hong; Shun-peng Li (Current Microbiology, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

The biological effects of hsa-miR-1908 in human adipocytes - Lei Yang; Chun-mei Shi; Ling Chen; Ling-xia Pang; Guang-feng Xu; Nan Gu; Li-jun Zhu; Xi-rong Guo; Yu-hui Ni; Chen-bo Ji (Molecular Biology Reports, 2015)

Mycoremediation potential and tolerance responses of Oudemansiella radicata in cadmium-pyrene co-contaminated soil - Rong Chen; Zhiren Zhou; Yuanxiu Liu; Juan Jiang; Qiao Li; Haihai Song; Donghui Pei; Heng Xu (Journal of Soils and Sediments, 2015)

Novel Interactive Partners of Neuroligin 3: New Aspects for Pathogenesis of Autism - Chen Shen; Li-rong Huo; Xin-liang Zhao; Pei-rong Wang; Nanbert Zhong (Journal of Molecular Neuroscience, 2015)

Polycyclic aromatic hydrocarbons associated with total suspended particles and surface soils in Kunming, China: distribution, possible sources, and cancer risks - Xiaoxia Yang; Dong Ren; Wenwen Sun; Xiaoman Li; Bin Huang; Rong Chen; Chan Lin; Xuejun Pan (Environmental Science and Pollution Research, 2015)

Modelling the effect of soil moisture variability on summer precipitation variability over East Asia - Zhongxian Li; Tianjun Zhou; Haishan Chen; Donghong Ni; Rong‐Hua Zhang (International Journal of Climatology, 2015)
The potential role of surface soil moisture ( SSM ) in improving the simulation of interannual East Asian summer precipitation is investigated using a coupled land‐atmosphere climate model, the Community Atmosphere Model version 3 ( CAM3 ). Forced by specified observational sea surface temperature ( SST ), two ensemble simulations for 22 boreal‐summer seasons (1979–2000) are conducted, one with interannually varying SSM ( SSM inter ) forcing and another with climatological SSM ( SSM clim ) forcing. Results show that, relative to the SSM clim run, interannual variability of East Asian summer precipitation is better simulated in the SSM inter run over the mid‐ and high‐latitudes of East Asia, especially in northwest China, where the correlation coefficient between precipitation simulated and observed from the Climate Prediction Center Merged Analysis of Precipitation (CMAP) is increased from 0.12 to 0.56 during 1979–2000. Meanwhile, positive relationships between anomalies of local soil evaporation and summer precipitation in northwest China can be better reproduced in the SSM inter run than in the SSM clim run. Possible mechanisms for the improved simulations of the interannual summer precipitation variability in northwest China are analysed; the improvement is resulted from the reasonable reproduction of anomalous atmospheric circulation in Siberia and Iranian plateau.

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Bacteriological and virulence study of a Mycobacterium chimaera isolate from a patient in China - Guan Liu; Su-Ting Chen; Xia Yu; Yu-Xun Li; Ying Ling; Ling-Ling Dong; Su-Hua Zheng; Hai-Rong Huang (Antonie van Leeuwenhoek, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)